Analisis Pelanggaran Etika Pariwara Indonesia (EPI) dalam Iklan Produk Komersial Televisi - Zhavira Handayani; Era Rahmadani Damanik; Riswan Rambe (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to examine violations of the Indonesian Advertising Code of Ethics (EPI) in television advertisements and explore the root causes of these violations. A qualitative approach was used, with data collection techniques including literature review, advertisement analysis, and exploration of digital sources such as YouTube, blogs, and online platforms. The study analyzes two advertisements in depth: SoKlin Sakura x Strawberry and Torabika Cappuccino coffee. The findings show that the SoKlin advertisement violates Article 1.26 of the Indonesian Advertising Code of Ethics (EPI) by using an unethical camera angle that highlights women's bodies, thereby containing subtle elements of sexual exploitation. Meanwhile, the Torabika advertisement was found to violate Article 1.2.2 of the EPI by making the superlative claim of being “number one in the world” without providing verifiable evidence. This violation is considered misleading to consumers and detrimental to the credibility of the advertisement. This study emphasizes the importance of adhering to advertising ethics codes, particularly in maintaining honesty, relevance, and social responsibility in every message communicated to the public.